Throughput modeling in IEEE 802.11 WLAN-based wireless networks - Kirill Ermolov (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2013)

(untitled)
Wireless Local Area Networks (WLANs) are nowadays the most widely used indoor wireless networks that found a large variety of wireless applications. WLANs are widely used in both home and office networking. Due to the ability of providing high data rate access, WLANs are significant components of next generation wireless networks. Next generation wireless networks must provide a reliable communication and high data rate under various scenarios. A way of solving these tasks is the application of adaptive methods where system characteristics change according to channel conditions. A reliable model of WLAN operation is required for design and analysis of adaptive rate adaptation methods. In this work, we created a simulation model that is used for analyzing WLAN throughputs under different scenarios. It can be also applied to analyze other important performance metrics such as the delay and probability of collisions.